Research and application of Web of things resource management framework - Yangqun LI; Dengyin ZHANG (物联网学报)
Web of things (WoT) connects all things together through the Web and realizes the sharing of resources, such as data or services provided by things, to fully implement their potential value.However, these resources are distributed in various places and belong to different organizations.The WoT resource management based on central infrastructure can no longer meet the new situation of continuous expansion of application scale, rapid changes in demand, and continuous increase of data types.In response to these new problems and new requirements, WoTRMF (Web of things resource management framework) was proposed.Firstly, based on this framework, the WoT resource management mechanism from the following aspects was reviewed, including distributed management of resources, efficient publish and discovery of resources, cost-effective, secure and efficient sharing of resources, and a unified resource management platform.Then, according to the requirement of distributed management, a P2P technology based on geographic location was proposed to realize distributed automatic management of WoT resources, so as to meet the high availability requirements of WoT applications and improve the efficiency of resource management.Aiming at the requirement of efficient resource publishing/discovery, an intelligent WoT resource publishing mechanism based on probabilistic topics was proposed to realize automatic classification and orderly publishing and storage of resources.Aiming at the security access requirements of resources, a secure and trusted WoT resource sharing mechanism based on blockchain was proposed.According to the requirement of unified resource management, the functional implementation model of WoTRMF was given.Finally, through the application case of WoTRMF framework in smart city security management, its characteristics of openness, flexibility, scalability and intelligence were analyzed.